2015
DOI: 10.1002/app.42885
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanical properties of a photocatalytic pseudo‐paint

Abstract: Photocatalytic oxidative paints (e.g., a paint containing nano-TiO 2 ) are used to break down volatile organic compounds to CO 2 by photooxidation reactions. In this research, a photocatalytic oxidative pseudo-paint was made with acrylic-styrene copolymer latex, TiO 2 pigment, calcium carbonate extender, and TiO 2 nanoparticles as a photocatalyst. To investigate the effects of the pigment, extender, and nanoparticles on the mechanical properties of the samples and their relationship to their photocatalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, the photocatalyst may cause oxidation of the organic constituents of the coating and compromise the integrity of the coating [13][14][15]. Despite these challenges, photocatalytic coatings have been used successfully for multiple applications, showing substantial activity towards photo-degradation of dyes, volatile organic compounds (VOCs), nitrogen oxide gases (NOx), bacteria and fungi [16][17][18][19][20][21][22][23][24][25]. It has been reported that photocatalytic coatings need a prior activation, usually a period of UV exposure for a certain time to induce binder photodegradation, to unleash their optimal performance [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the photocatalyst may cause oxidation of the organic constituents of the coating and compromise the integrity of the coating [13][14][15]. Despite these challenges, photocatalytic coatings have been used successfully for multiple applications, showing substantial activity towards photo-degradation of dyes, volatile organic compounds (VOCs), nitrogen oxide gases (NOx), bacteria and fungi [16][17][18][19][20][21][22][23][24][25]. It has been reported that photocatalytic coatings need a prior activation, usually a period of UV exposure for a certain time to induce binder photodegradation, to unleash their optimal performance [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…After the authors’ previous report on the mechanical properties of a photocatalytic pseudo‐paint, this article addresses application of PCO technology in interior paint and elucidates the role of two main paint components (pigment and extender) along with nanoparticles on PCO. Another target of this article is to study how the mechanical properties variate during time of UV exposure.…”
Section: Introductionmentioning
confidence: 99%